Polymorphisms in IL10 may alter CD4 T-cell counts in Indonesian HIV patients beginning antiretroviral therapy - Dmello, D.; Ariyanto, I.; Estiasari, R.; Halstrom, S.; Gaff, Jessica; Lee, S.; Price, Patricia (Elsevier Inc., 2017)
Interleukin 10 (IL-10) is a potent anti-inflammatory cytokine influenced by single nucleotide polymorphisms (SNP) located in upstream regulatory regions. Here we address the effects of five SNP (rs1518111, rs3021094, rs3024491, rs1800872 and rs1800871) on CD4 T-cell counts in Indonesian HIV patients assessed before ART and over 12 months on treatment. Heterozygosity at rs1518111 or rs1800872 associated with low CD4 T-cell counts at all time points. Both alleles were carried in two haplotypes. Haplotype 21122 (present in 30% of participants) associated with low CD4 T-cell counts, whereas 21222 (in 6% of participants) did not. Hence untyped SNP(s) tagged by 21122 may depress CD4 T-cell counts. The association with heterozygosity suggests synergy with an allele from a haplotype lacking rs1518111 and/or rs1800872.